Induction of Immune Tolerance in a 7-Year-Old Hemophiliac with an Anaphylactoid Inhibitor - Harper, James L; Gill, Joan C; Hopp, Russell J; Evans, John; Haire, William D (Thrombosis and Haemostasis, 1995)
Background: Anaphylactic reactions were a rare complication of low purity VIII concentrates, hut not with high purity VIII concentratesCase: 7 y/o WM with severe hemophilia A, received only cryoprecipitate and monoclonally purified VIII concentrates; developed post-infusional urticaria. A 2-Bethesda-unit inhibitor was detected. Generalized urticaria and bronchospasm following factor developed as the titer increased. Skin tests demonstrated reactivity to plasma derived VIII, but not recombinant VIII (rhVIII). Attempts at desensitization using rhVIII failed. KLISA revealed an anti-VIIl IgB antibody. He was treated with a modified tolerance regimen using rhVIII starting at 500 U/day with aggressive premedication. The dosage increased by 200 U weekly as tolerated to a maximum of l00U/kg/d without symptoms. Results: His antibody titer decreased rapidly once he started l00U/kg/d. Six months later, the inhibitor was <1 Bethesda unit. Conclusion: Immune tolerance induction using a graduated dosage of rhVIII was successful.